Reversed Gender Roles and Linguistic Choices: A Transitivity Analysis of Gender Disparities in Ali’s The Stone Woman - Anwar, Behzad; Kayani, Asma Iqbal; Ramiz, Muhammad (Journal of Development and Social Sciences, 2024)
The present study is a critique of the language used in a literary text i.e., The Stone Woman (2000) written by Tariq Ali, a famous Pakistani-British writer in order to find out gender disparities through transitivity analysis. For the purpose two characters, Nilofer and Selim, the female and male participants of romance scenes are selected. Following a mixed method approach, the study has collected fifty clauses as sample through purposive sampling. The greater number of clauses i.e., thirty clauses used to represent the female while the lesser number i.e., twenty clauses for the male show a biased attitude of the writer. The analysis shows that the female is described through a maximum use of all the four identified types of clauses: fifty-eight percent material, sixty percent mental, sixty-seven percent behavioral and sixty-seven percent verbal. In comparison to this the clauses used to describe the male appear with lesser frequency: forty-two percent material, forty percent mental, and thirty-three percent behavioral and verbal each. Moreover, the allocation of the participants’ roles with power and authority are mostly reserved for the female: fifty-eight percent actor ,sixty percent senser , sixty-seven percent sayer while the male is shown less active through maximum fifty-nine percent goal and sixty seven percent receiver roles. The findings of the study clearly show that Nilofer is more dominant and authoritative in the romance scenes as compared to Selim who is reluctant and acts only when he is encouraged by the female. Hence, the study finds that the traditionally reserved gender roles are reversed in Ali’s The Stone Woman.